Efektivitas Model Think-Talk-Write dalam Pembelajaran Menulis Argumentasi Siswa SMP Negeri 1 Gunungsari - Shakira Khansa Aulia; Indah Pratiwi (Educational Note, 2025)
This study aims to determine the effectiveness of the Think-Talk-Write (TTW) learning model in improving the argumentative writing skills of eighth-grade students at SMP Negeri 1 Gunungsari. Argumentative writing is a higher-level language skill that requires critical thinking ability, systematic logical organization, and the capacity to present ideas persuasively. However, preliminary observations revealed that many students experienced difficulties in developing ideas and constructing coherent arguments. This research employed a quantitative approach with a quasi-experimental design, involving two classes: an experimental class that received instruction using the TTW model and a control class that was taught using a conventional learning model. The research instrument consisted of an argumentative writing test, which was analyzed using a t-test to determine whether there was a significant difference between the two groups. The results of the study indicate that students who were taught using the TTW model showed a significant improvement in the quality of their argumentative writing, particularly in terms of argument structure, content relevance, and language use. The TTW model proved to effectively facilitate the development of critical thinking through its integrated stages of thinking, talking, and writing. Therefore, the TTW model is recommended as an effective alternative instructional strategy for teaching writing at the junior high school level, particularly for the development of argumentative writing skills.